Effects of different pollination methods on tomato fruits’ quality and metabolism - Ma, Wei-Hua; Wu, Wen-Qin; Song, Huai-Lei; Lei, Jia; Li, Li-Xin (Frontiers in Plant Science, 2025)
Bee pollination can affect tomato yield and quality. The mechanism of improving the yield and quality of tomatoes by bee pollination is not clear, and few studies have been conducted. To understand how bee pollination affects tomato quality, by using respectively weighing, vernier caliper, handheld refractometer, pH meter to measure single fruit weight, fruit size, the sugar content, and the pH value, enzyme linked immunosorbent assay (ELISA) to determine endogenous hormone content, and LC-MS to perform untargeted metabolomics analysis, we compared these physiological indicators, endogenous hormone levels, and metabolism of tomato fruits pollinated after honeybee, bumblebee, and plan growth regulator (PGR) pollination. Our results indicate that the tomatoes pollinated by bumblebees were heavier and larger than those pollinated by honeybees and PGR. The sugar content of tomatoes pollinated by honeybees and bumblebees significantly respectively increased by 7.96% and 10.18% than that of tomatoes pollinated by PGR. The pH value of tomatoes pollinated by honeybees (3.99 ± 0.02) and bumblebees (3.94 ± 0.03) was significantly lower than that of tomatoes pollinated by PGR (4.19 ± 0.04) (p < 0.05). Different pollination methods significantly affected the content of endogenous hormones in fruits. In five endogenous hormones, the highest content was gibberellin (GA) in honeybee pollination treatment, IAA in bumblebee treatment, and the highest contents were abscisic acid (ABA), zeatin (ZT), and N6-(Δ2-isopentenyl) adenosine (iPA) in PGR treatment. It is speculated that different pollination methods may regulate the maturity and quality of tomatoes through different hormone levels. There were respectively five different metabolites (three upregulated and two downregulated), 95 different metabolites (59 upregulated and 36 downregulated), and 95 different metabolites (56 upregulated and 39 downregulated) in honeybee pollination vs. bumblebee pollination, honeybee pollination vs. PGR pollination, and bumblebee pollination vs. PGR pollination. Metabolites are mainly involved in phenylpropanoid biosynthesis, flavonoid biosynthesis pathway, and stilbenoid, diarylheptanoid and gingerol biosynthesis. Compared with PGR pollination, the metabolism of amino acids, vitamins, sugars, flavor substances, and organic acids with antioxidant physiological effects in honeybee pollination and bumblebee pollination groups was significantly higher. It can be inferred that the tomato fruit after bee pollination may have a better taste and is favorable to resisting diseases. These results provide valuable insight for uncovering the mechanism of how bee pollination enhances tomato fruit flavor and will enhance our understanding of interactions between bee pollinators and fruit development processes.